2013
DOI: 10.1038/ni.2714
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factors enhance the effector responses of CD8+ T cells to persistent antigen

Abstract: Cytolytic activity by CD8+ cytotoxic T lymphocytes (CTLs) is a powerful strategy for the elimination of intracellular pathogens and tumor cells. The destructive capacity of CTLs is progressively dampened during chronic infection, yet the environmental cues and molecular pathways that influence immunological `exhaustion' remain unclear. Here we found that CTL immunity was regulated by the central transcriptional response to hypoxia, which is controlled in part by hypoxia-inducible factors (HIFs) and the von Hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
562
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(609 citation statements)
references
References 51 publications
(63 reference statements)
40
562
4
3
Order By: Relevance
“…In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 . Similarly, disrupting the von Hippel-Lindau tumor suppressor (VHL) gene causes overwhelming immunopathology by enforcing cytotoxic activity of T-cells in persisting infections 78 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 99%
“…In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 . Similarly, disrupting the von Hippel-Lindau tumor suppressor (VHL) gene causes overwhelming immunopathology by enforcing cytotoxic activity of T-cells in persisting infections 78 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 99%
“…We next sought to determine the mechanism by which proteasome activity influences the glycolytic transcriptional program. Several key transcription factors, including Myc, estrogen-related receptor α (ERRα), and hypoxia-inducible factor 1-α (HIF1α), have been shown to facilitate metabolic reprogramming by upregulating genes associated with the glycolytic pathway (1,(40)(41)(42). Conversely, Bcl-6 directly represses genes encoding the glycolytic pathway, while Foxo1 positively regulates genes involved in mitochondrial function and fatty acid metabolism (43,44).…”
Section: Proteasome Activity Influences Transcriptomic and Proteomicmentioning
confidence: 99%
“…For instance, the increased glycolytic metabolism promotes effector T-cell generation (11), whereas oxidative phosphorylation and mitochondrial spare respiratory capacity facilitate memory T-cell differentiation (12,13). Recent studies have also identified transcriptional regulators of cell metabolism that promote effector T-cell differentiation, including HIF1 and IRF4 (14)(15)(16)(17). In contrast, how cell metabolism is regulated by immune signaling pathways in effector and memory T-cell differentiation remains unclear.…”
mentioning
confidence: 99%